Loan Loss Provision Research on Chinese banks and Hypotheses Tests - Zhang, Hanlin (2017)
This paper mainly investigates the loan loss provision behavior in Chinese bank sectors from 2011 to 2016. This paper examines the income smoothing, capital management, business cycle and efficiency hypotheses the results indicate that Chinese commercial banks are detected to utilize loan loss provision for earning management, and loan loss provision totally shows a pro-cyclical trend. The improvement of banks’ cost efficiency would decrease the loan loss provision need to be prepared. Further research finds that listed commercial banks have less motivation to manage income for the risk-shift reason. The is no evidence found to indicate the relationship between loan loss provisions and capital managements.